Muslims in the West - edited by Yvonne Yazbeck Haddad (Oxford University Press, 2002)
Today, Muslims are the second largest religious group in much of Europe and North America. The essays in this collection look both at the impact of the growing Muslim population on Western societies, and how Muslims are adapting to life in the West. Part I looks at the Muslim diaspora in Europe, comprising essays on Britain, France, Germany, Switzerland, Norway, Sweden, Denmark, Italy, and the Netherlands. Part II turns to the Western Hemisphere and Muslims in the U.S. , Canada, and Mexico. Throughout, the authors contend with such questions as: Can Muslims retain their faith and identity and at the same time accept and function within the secular and pluralistic traditions of Europe and America? What are the limits of Western pluralism? Will Muslims come to be fully accepted as fellow citizens with equal rights? An excellent guide to the changing landscape of Islam, this volume is an indispensable introduction to the experiences of Muslims in the West, and the diverse responses of their adopted countries